Breast metastasis as the first presentation of an anorectal melanoma diagnosed on fine needle aspiration cytology: a case report - Adil Aziz Khan; Shaivy Malik; Sana Ahuja; Mukul Singh (BMC, 2023)
Abstract Background Primary anorectal melanoma is a rare and aggressive disease accounting for approximately 1-3% of all colorectal and anal cancers. Case report We present a unique case of anorectal melanoma where the primary presentation was the metastatic breast lump which led to the detection of the primary tumor. A 70-year-old elderly postmenopausal female presented with complaint of left breast lump. On fine needle aspiration cytology, May Grunwald-Giemsa and Papanicolaou stained smears examined were highly cellular and showed sheets, clusters and singly scattered highly pleomorphic plasmacytoid cells having high nucleus to cytoplasmic ratio and scant to moderate cytoplasm with enlarged eccentric round to ovoid nuclei. Immunocytochemistry performed on cell block preparation showed tumor cells strongly positive for HMB-45, S-100 and negative for ER, PR, Her2neu, chromogranin, synaptophysin and Pan-CK. A thorough work up of the patient to look for the site of primary malignancy was done and radiological findings reveled presence of an ill-defined soft tissue mass in the anal canal. Biopsy from the anal mass confirmed the diagnosis of anal melanoma with metastasis to breast. Conclusion The present case was reported to emphasize the importance of atypical presentation where the breast lump was the primary presentation of an anal melanoma. Therefore, we should have a strong index of suspicion for metastatic tumors in case of a breast lump especially when there is unusual morphology or unexpected immunophenotype, particularly if the neoplasm is triple-negative, in patients with a previous history of other malignancies.